Roads as a contributor to landscape-scale variation in bird communities - Sophia C. Cooke (Nature Portfolio, 2020)
Roads are widespread and can impact ecological communities. Cooke et al. use data for 75 bird species across Great Britain to show that common species are disproportionately abundant near roads, whereas rarer, smaller-bodied and migrant species are more likely to be negatively associated with roads.